2019
DOI: 10.1021/acsami.9b14481
|View full text |Cite
|
Sign up to set email alerts
|

White Eggshells: A Potential Biowaste Material for Synergetic Adsorption and Naked-Eye Colorimetric Detection of Heavy Metal Ions from Aqueous Solution

Abstract: In the present work, we have utilized a simple, no-cost, unmodified eggshell powder as a naked-eye colorimetric detector, which on simple dispersion in aqueous solution of metal ions exhibited characteristic color change from white to pale green, pale blue, yellow, pale yellow, dark yellow, pale pink, blue, and brown for metal ions V 4+ , Cr 3+ , Cr 6+ , Fe 2+ , Fe 3+ , Co 2+ , Cu 2+ , and Ag + , respectively. The effects of various parameters like concentration of metal ions, pH, temperature, and adsorbent do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Many researchers are working in this eld for the development of selective detection of transition and heavy metal ion impurities. From the different available detection methods such as colorimetry, [128][129][130] mass spectrometry, [131][132][133] atomic absorption spectroscopy, 134-136 electrochemical [137][138][139][140] and uorescence 141-145 methods, the uorescence methods are the most reliable and effective because of their high sensitivity, high efficiency, and operative simplicity. Praethong Laopa and Tirayut Vilaivan 40 synthesized cationic polymer-coated ZnO QDs for the selective detection of the Fe(II) ion.…”
Section: Detection Of Metal Ionsmentioning
confidence: 99%
“…Many researchers are working in this eld for the development of selective detection of transition and heavy metal ion impurities. From the different available detection methods such as colorimetry, [128][129][130] mass spectrometry, [131][132][133] atomic absorption spectroscopy, 134-136 electrochemical [137][138][139][140] and uorescence 141-145 methods, the uorescence methods are the most reliable and effective because of their high sensitivity, high efficiency, and operative simplicity. Praethong Laopa and Tirayut Vilaivan 40 synthesized cationic polymer-coated ZnO QDs for the selective detection of the Fe(II) ion.…”
Section: Detection Of Metal Ionsmentioning
confidence: 99%
“…21 Another interesting attempt shows that eggshell powder could be exploited as a colorimetric detector for the successful detection and discrimination of 10 ions from aqueous solution through physical adsorption. 22 By further analyzing the colorimetric sensing principle, it is promising if one could consider the design of a versatile colorimetric reagent with great sensitivity and accuracy for the detection and identification of multiple military and improvised explosives, no matter whether they are water-soluble or water-insoluble.…”
mentioning
confidence: 99%
“…From the colorimetric sensing material design aspect, multicolorimetric sensors, typically based on target molecule-guided etching and the change of the noble metal nanostructure color that could reflect the exact species of the target molecules, have been widely used for visual inspection applications . Another interesting attempt shows that eggshell powder could be exploited as a colorimetric detector for the successful detection and discrimination of 10 ions from aqueous solution through physical adsorption . By further analyzing the colorimetric sensing principle, it is promising if one could consider the design of a versatile colorimetric reagent with great sensitivity and accuracy for the detection and identification of multiple military and improvised explosives, no matter whether they are water-soluble or water-insoluble.…”
mentioning
confidence: 99%
“…It was found that the incorporation of nutrients decreased the pore volume due to the blockage of pores by incorporation of nutrient elements. 13 Also, compared to ES, the BET surface area of ES-SMF decreased, which demonstrated that the macro-and micronutrients occupied the pores in ES. The heat of adsorption was found to be less than 50 KJ/mol, which indicates that the interactions are physisorption.…”
Section: Resultsmentioning
confidence: 52%